IMPELENTASI STRATEGI PEMASARAN RASULULLAH DALAM KONTEKS KONTEMPORER (Analisis di Swalayan Pamella Yogyakarta dan La Tansa Gontor Ponorogo) - Abdullah Sahroni (Millah: Journal of Religious Studies, 2015)
Rasulullah’s Marketing strategy based on Muhammad Suyanto book “Muhammad Bisuness Strategy and Ethics” are; product strategy is halalan thayyiban goods, price strategy based on the principle of concensual and market’s price, place positioning is preferred in the market and strategys place and promotion strategy is more emphasis on the relationship with the costumer. This research is meant to scrutinize and understand rasulullah’s marketing strategy at Pamella minimarket and La Tansa. This research concluded that Pamella minimarket and La Tansa has implementated marketing strategy of product, price, place and promotion based on Rasulullah’s strategy with improvement era with Islamic value. Marketing strategy at Pamella minimarket and La Tansa is in conformity with Rasulullah’s marketing strategy keeping the values taught by the Prophet Muhammad such as; honesty, customer satisfaction, market segmentation, positioning and pricing strategy.